Feeling right is feeling good: psychological well-being and emotional fit with culture in autonomy- versus relatedness-promoting situations - De Leersnyder, Jozefien; Kim, Heejung; Mesquita, Batja (Frontiers in Psychology, 2015)
The current research tested the idea that it is the cultural fit of emotions, rather than certain emotions per se, that predicts psychological well-being. We reasoned that emotional fit in the domains of life that afford the realization of central cultural mandates would be particularly important to psychological well-being. We tested this hypothesis with samples from three cultural contexts that are known to differ with respect to their main cultural mandates: a European American (N = 30), a Korean (N = 80), and a Belgian sample (N = 266). Cultural fit was measured by comparing an individual’s patterns of emotions to the average cultural pattern for the same type of situation on the Emotional Patterns Questionnaire (De Leersnyder, Mesquita, & Kim, 2011). Consistent with our hypothesis, we found evidence for “universality without uniformity”: In each sample, psychological well-being was associated with emotional fit in the domain that was key to the cultural mandate. However, cultures varied with regard to the particular domain involved. Psychological well-being was predicted by emotional fit a) in autonomy-promoting situations at work in the U.S., b) in relatedness-promoting situations at home in Korea, and c) in both autonomy-promoting and relatedness-promoting situations in Belgium. These findings show that the experience of culturally appropriate patterns of emotions contributes to psychological well-being. One interpretation is that experiencing appropriate emotions is itself a realization of the cultural mandates.